2016
DOI: 10.1021/acs.jmedchem.5b01984
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent Benzofuran-Derived Diapophytoene Desaturase (CrtN) Inhibitors with Enhanced Oral Bioavailability for the Treatment of Methicillin-Resistant Staphylococcus aureus (MRSA) Infections

Abstract: Blocking the staphyloxanthin biosynthesis process has emerged as a new promising antivirulence strategy. Previously, we first revealed that CrtN is a druggable target against infections caused by pigmented Staphylococcus aureus (S. aureus) and that naftifine was an effective CrtN inhibitor. Here, we identify a new type of benzofuran-derived CrtN inhibitor with submicromolar IC50 values that is based on the naftifine scaffold. The most potent analog, 5m, inhibits the pigment production of S. aureus Newman and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 19 publications
0
56
0
Order By: Relevance
“…Many studies revealed that the knockout of crtM or crtN could significantly repress the production of STX ( Liu et al, 2008 ; Liu and Nizet, 2009 ). Thus, the block of the STX biosynthesis process has proposed as an alternative anti-virulence therapy, in which crtM and crtN are target for drugs used in the treatment of infections caused by pigmented S. aureus ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies revealed that the knockout of crtM or crtN could significantly repress the production of STX ( Liu et al, 2008 ; Liu and Nizet, 2009 ). Thus, the block of the STX biosynthesis process has proposed as an alternative anti-virulence therapy, in which crtM and crtN are target for drugs used in the treatment of infections caused by pigmented S. aureus ( Wang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, 19 was approved for external application, and the moderate pigment inhibitory effect, poor pharmacokinetics (PK) data, and low oral bioavailability ( F value) limited its use to become a potential antivirulence candidate against MRSA infection. In this section of the serial work, our aim was to deliver an orally efficacious CrtN inhibitor by optimizing the scaffold of 19 , followed by obtaining a series of novel 19 analogs possessing independent intellectual property rights . First, chemical modifications were performed in four cycles.…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 99%
“…Further SAR analysis of the derivatives of 19 provided important insights into the essential structural requirements for effective pigment inhibition as follows: (a) the naphthyl moiety of 19 was not indispensable for pigment inhibitory activity; indeed, the replacement of the naphthyl ring with other similar bulky aromatic rings such as benzofuran and quinoline can be tolerated ( 19 vs 26 , 27 or 28 ); (b) in region A, the N ‐methyl group was critical for high potency, and functional groups that were too small or too large were not beneficial, leading to a loss of pigment inhibitory activity; and (c) in region B of the compounds, among the different linkers, the potency decreased in the following order: 1,3‐pentadienyl > propargyl > allyl > 2‐methyl allyl = propyl = methenecyclopropanyl. Due to the structural change in the benzofuran analogs, we testified whether benzofuran‐derived 29 ( 5 m) had the same target as CrtN inhibitor 19 through a similar HPLC assay as described previously. CrtN enzymatic inhibition assays further confirmed that 29 and other representative analogs were all CrtN inhibitors with submicromolar IC 50 values, being more effective than either 19 or DPAs previously reported.…”
Section: Pigments Of Representative Colored Pathogens and Their Inhibmentioning
confidence: 99%
See 1 more Smart Citation
“…19 On the basis of the results above, we further designed and synthesized a series of novel benzofuran and benzocycloalkane CrtN inhibitors, from which the efficient derivatives 3 and 4 were obtained (Figure 1). 20,21 Moreover, analogue 4a displayed excellent potency in vitro (pigment inhibition: IC 50 = 1.9 nM, Figure 1) but was still limited by its strong inhibition of human Ether-a-go-go Related Gene (hERG), high required dosage, and moderate water solubility in subsequent investigations. 21 Therefore, in this study, a novel compound was designed and synthesized to overcome the defects of lead compound 4a.…”
mentioning
confidence: 99%